Vertical sleeve gastrectomy associates with airway hyperresponsiveness in a murine model of allergic airway disease and obesity - Womble, Jack T.; Ihrie, Mark D.; McQuade, Victoria L.; Hegde, Akhil; McCravy, Matthew S.; Phatak, Sanat; Tighe, Robert M.; Que, Loretta G.; D’Alessio, David; Walker, Julia K. L.; Ingram, Jennifer L. (Frontiers in Endocrinology, 2023)
Asthma is a chronic airway inflammatory disease marked by airway inflammation, remodeling and hyperresponsiveness to allergens. Allergic asthma is normally well controlled through the use of beta-2-adrenergic agonists and inhaled corticosteroids; however, a subset of of patients with comorbid obesity experience resistance to currently available therapeutics. Patients with asthma and comorbid obesity are also at a greater risk for severe disease, contributing to increased risk of hospitalization. Bariatric surgery improves asthma control and airway hyperresponsiveness in patients with asthma and comorbid obesity, however, the underlying mechanisms for these improvements remain to be elucidated. We hypothesized that vertical sleeve gastrectomy (VSG), a model of metabolic surgery in mice, would improve glucose tolerance and airway inflammation, resistance, and fibrosis induced by chronic allergen challenge and obesity. Male C57BL/6J mice were fed a high fat diet (HFD) for 12 weeks with intermittent house dust mite (HDM) allergen administration to induce allergic asthma, or saline as control. At week 10, a subset of mice underwent VSG or Sham surgery with one week recovery. A separate group of mice did not undergo surgery. Mice were then challenged with HDM or saline along with concurrent HFD feeding for 2 weeks before measurement of lung mechanics and harvesting of tissues, both of which occurred 48 hours after the final HDM challenge. Systemic and pulmonary cytokine profiles, lung histology and gene expression were analyzed. High fat diet contributed to increased body weight and development of glucose intolerance for both HDM and saline treatment groups. When compared to saline-treated mice, HDM-challenged mice had higher weight gain. VSG improved glucose intolerance for saline treated mice, but not in HDM-challenged mice when comparing post-surgical and pre-surgical glucose tolerance tests. HDM-challenged VSG mice exhibited an increase in airway hyperresponsiveness to methacholine when compared to the non-surgery group. The data presented here indicate increased airway hyperresponsiveness in allergic mice undergoing bariatric surgery.